Estimation of the chlorophyll-a concentration on the surface of Sechura Bay using Landsat 8 image data - Ramírez, Gilberto (2021)
The purpose of this study is to implement the OC2 and OC3 algorithms to estimate the concentration of surface chlorophyll-a (CCA) from image data from the OLI sensor aboard the Landsat-8 satellite. The LaSRC (Landsat 8 Surface Reflectance Code) atmospheric correction model was validated with on-site measurements of the reflectance of the water surface recorded with a spectroradiometer on the surface of the fan shell crop area of the Sechura Bay. Validation results in a linear correlation coefficient of R = 95.1 % and a mean square error RMSE = 0.0095. A comparison of the CCA derived from the OC2 and OC3 algorithms was also made, resulting in an RMSE = 0.145 mg/m3 and a correlation coecient of R = 99 %. Finally, a contrast was made of the histograms of the spatial distribution of the CCA estimated from the OC2 and OC3 algorithms over a region of the study area. The results indicate a greater ability to discern the OC3 algorithm compared to the OC2 algorithm